Activation for the Elderly Through the Modernization of Their Homes – for Example, Multifamily Housing from Katowice - Benek, Iwona (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Multi-family housing from 30, 40 years ago will need a general overhaul in the immediate future. Along with the overhaul a modernization of such flats is needed creating the perfect opportunity to adapt them to the needs of the older. It has been assumed that the main course of action is to examine the existing housing space in order to specify the spatial conditions crucial for the integration of the older people and to analyze the technical possibility of adaptation.